Experimental Investigations on Aircraft Blade Cooling Holes and CFD Fluid Analysis in Electrochemical Machining - Mingxia Chai; Zhiyong Li; Hongjuan Yan; Xiaoyu Sun (Advances in Materials Science and Engineering)
The flow field distribution in an interelectrode gap is one of the important factors that affect the machining accuracy and surface quality in the electrochemical machining (ECM) process for aircraft blades. In the ECM process, some process parameters, e.g., machining clearance, processing voltage, and solution concentration, may result in electrolyte fluid field to be complex and unstable, which makes it very difficult to predict and control the machining accuracy of ECM. Therefore, 30 sets of experiments for cooling hole making in ECM were carried out, and furthermore, the machining accuracy and stability of cooling hole were concentrated. In addition, the flow channel of the geometrical model of the gap flow field was established and analyzed according to the electrolyte flow state simulation by CFD. The effects of the flow velocity mode on the machining accuracy and stability for cooling hole making were investigated and determined in detail.